2011
DOI: 10.1155/2011/953412
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Dental Caries and the Salivary Proline-Rich Proteins

Abstract: Early childhood caries affects 28% of children aged 2–6 in the US and is not decreasing. There is a well-recognized need to identify susceptible children at birth. Caries-free adults neutralize bacterial acids in dental biofilms better than adults with severe caries. Saliva contains acidic and basic proline-rich proteins (PRPs) which attach to oral streptococci. The PRPs are encoded within a small region of chromosome 12. An acidic PRP allele (Db) protects Caucasian children from caries but is more common in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 85 publications
0
37
0
4
Order By: Relevance
“…The N-terminal domain ensures coupling of APRP-1/2 to hydroxyapatite and formation of the acquired enamel pellicle. In parallel the C-terminal domain of APRP-1/2 binds to oral bacteria, promoting bacterial colonization of dental surface, which may play a significant role in pathogenesis of caries [9,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal domain ensures coupling of APRP-1/2 to hydroxyapatite and formation of the acquired enamel pellicle. In parallel the C-terminal domain of APRP-1/2 binds to oral bacteria, promoting bacterial colonization of dental surface, which may play a significant role in pathogenesis of caries [9,20].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, it is well known that APRP-1/2 manifest high affinity for hydroxyapatite and are involved in the formation of dental-acquired pellicle [6][7][8]. It is also suggested that salivary APRPs may affect susceptibility to dental caries [9].…”
Section: Introductionmentioning
confidence: 99%
“…Basic PRP's in whole saliva attaches to the major adhesion antigen on surface of S.Mutans, protecting the surface of tooth from caries.Thus greater the basic PRP's greater the adhesion and acid neutralization in biofilms. These proteins adhere strongly to the tooth surface and expose a previously cryptic binding site for bacteria within the non -binding C-terminal domain [3].…”
Section: Estimation Of Mucin Levelsmentioning
confidence: 99%
“…38 Acidic PRPs are encoded by two genes, PRH1 and PRH2, with three different alleles at PRH1 (Db, Pa, and Pif). 39 When the allele Db was studied, 20 it was present in 72% of African Americans and in 26% of Caucasians. Curiously enough, large groups of African American children, regardless of the presence of Db, had significantly less caries experience than Caucasian subjects (p < 0.01).…”
Section: Records Identified Through Database Search (N= 424)mentioning
confidence: 99%